Job Satisfaction Studying Healthcare Workers’ Satisfaction During COVID-19 Pandemic Using Factor Analysis - Hidayat, Arif Fatah; Agustina, Tri Siwi (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Hospital services are inseparable from the role of healthcare workers. Their job satisfaction is really important because satisfied healthcare workers will provide excellent service for patients andthe publicin general, and eventually may increase the value of the hospital. The motivation to conduct a study on this subject is the lack of previous studies about the job satisfaction of healthcare workers other than doctors and nurses during the COVID-19 pandemic. This study is a quantitative study that aims to determine factors that form healthcare workers’ job satisfaction. The respondents in this study include 157 healthcare workers in AisyiyahGeneral Hospital Ponorogofrom January to February 2021. The test of factor analysis was conducted by using SPSS version 2.0. The results show that the factors which form healthcare workers’ job satisfaction include: salary and benefit factor, work environment, leadership, the opportunity to grow, and the job itself.